2009
DOI: 10.1016/j.str.2008.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid Protease Dynamics and Lipid Interactions

Abstract: Summary Intramembrane proteases, which cleave TM helices, participate in numerous biological processes encompassing all branches of life. Several crystallographic structures of Escherichia coli GlpG rhomboid protease have been determined. In order to understand GlpG dynamics and lipid interactions in a native-like environment, we have examined the molecular dynamics of wild-type and mutant GlpG in different membrane environments. The irregular shape and small hydrophobic thickness of the protein cause signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
150
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(160 citation statements)
references
References 46 publications
(108 reference statements)
8
150
2
Order By: Relevance
“…It is more likely that loop 1 plays a role in "finetuning" the function of the receptor 41 possibly via orientation in the lipid bilayer. 36 With the substrate approaching the active site from the opposite side of the peptidase compared with our earlier prediction, 24 and given the architecture for the active-site residues, we predict that the mechanism for substrate cleavage will be similar, with the exception that the scissile bond of the substrate will be attacked on its si-face 25 (Fig. S2a).…”
Section: New Rhomboid Reaction Pathwaymentioning
confidence: 60%
See 1 more Smart Citation
“…It is more likely that loop 1 plays a role in "finetuning" the function of the receptor 41 possibly via orientation in the lipid bilayer. 36 With the substrate approaching the active site from the opposite side of the peptidase compared with our earlier prediction, 24 and given the architecture for the active-site residues, we predict that the mechanism for substrate cleavage will be similar, with the exception that the scissile bond of the substrate will be attacked on its si-face 25 (Fig. S2a).…”
Section: New Rhomboid Reaction Pathwaymentioning
confidence: 60%
“…Indeed, molecular dynamics simulations have shown that E. coli rhomboid protease can induce thinning and deformations of lipid bilayers. 36 Additional studies revealed that the substrate recognition motif need not be embedded in the bilayer for cleavage to occur. 34,37 In an alternative model, Baker et al 30 and Urban and Baker 38 postulated that a movement of helix 5 away from the rhomboid central helical bundle permits access of the substrate to the active-site residues.…”
Section: Discussionmentioning
confidence: 99%
“…The exact order of events, and what triggers each step, remain speculative. Membrane thinning surrounding GlpG as observed in molecular dynamics simulations is illustrated (Bondar et al, 2009; Zhou et al, 2012), although its functional consequence remains unclear. Structures 2IC8 (closed GlpG), 2NRF (open GlpG), 1MOX (Spitz-EGF), and 2TGF (TGFα-EGF) were used to diagram the model. DOI: http://dx.doi.org/10.7554/eLife.00173.016…”
Section: Discussionmentioning
confidence: 93%
“…S8), supporting the notion that these residues in HL1 play an important role in the processive cleavage activity of γ-secretase. The dynamic motion of the HL in rhomboid protease, the other intramembrane cleaving enzyme, influences the whole conformation and activity of the rhomboid (44). In addition, allosteric activation of the Vibrio cholerae repeats-in-toxin cysteine protease by inositol hexakisphosphate has been reported (45).…”
Section: Discussionmentioning
confidence: 99%